1992
DOI: 10.1346/ccmn.1992.0400605
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Structural Iron in Ferruginous Smectite by Free Radicals

Abstract: Abstract--The oxidation state of structural iron greatly influences the physical-chemical properties of clay minerals, a phenomenon that may have significant implications for pollutant fate in the environment, for agricultural productivity, and for industrial uses of clays. Knowledge of redox mechanisms is fundamental to understanding the underlying basis for iron's effects on clays. Past studies revealed that the extent of Fe reduction varied depending on the reducing agent used, but this variation may not ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…The model of Gan et al (1992) Electron spin resonance (ESR) spectroscopy was used to determine the reductant species responsible for the transfer of electrons during reduction. In solution, sodium dithionite (Na28204) dissociates to Na § and (8204) 2 ions.…”
Section: O~-+ H~ + -~ (Oh)~ (I)mentioning
confidence: 99%
See 1 more Smart Citation
“…The model of Gan et al (1992) Electron spin resonance (ESR) spectroscopy was used to determine the reductant species responsible for the transfer of electrons during reduction. In solution, sodium dithionite (Na28204) dissociates to Na § and (8204) 2 ions.…”
Section: O~-+ H~ + -~ (Oh)~ (I)mentioning
confidence: 99%
“…The disulfite anion also dissociates in water, partly according to 2($zO4) 2 + H20 --~ (8203) 2 + 2(HSO3)---* ($203) 2-+ 2(803) 2 -{-2H +, and partly into the paramagnetic free radical species, SO2 -~ which contains unpaired electrons as indicated here by "o" (Dunitz, 1956;Lynn et al, 1964;Rinker et al, 1958). Gan et al (1992) showed that in Na28204 solutions, these free radicals are responsible for the reduction of structural Fe 3+. They observed a correlation between the concentration of SO2-" in solution and the reducing ability of the reagent.…”
Section: O~-+ H~ + -~ (Oh)~ (I)mentioning
confidence: 99%
“…Dithionite is a high production volume chemical, primarily because of its industrial use in bleaching wood pulp (Dence 1996;Ellis 1996;Lindholm 1999;Pemberton, et al 1995) and its use in dyeing textiles, which helps to maintain its relatively low price of $0.76/lb (The Innovation Group 2008). In addition to its industrial uses, dithionite is widely used by soil scientists to reductively extract iron from soils (Gan et al 1992). The ability to reduce iron has also been applied to developing in situ aquifer remediation technology where iron in aquifer solids is reduced by dithionite and the reduced iron subsequently reduces oxidized contaminants (Szecsody et al 2004;Ludwig et al 2007).…”
Section: Nitrate (Nomentioning
confidence: 99%
“…Hydrogen sulfide is highly reactive, causing the reductive dissolution of some amorphous and poorly crystalline Fe(III) oxides (e.g., ferrihydrite) and the subsequent precipitation of the Fe(II) as amorphous FeS (Matsunaga et al 1993). The reduction of structural Fe(III) in layer silicates without dissolution may also occur (Gan et al 1992). These reduced phases store reductive capacity in sediments and subsequently can reduce soluble contaminants such as Cr(VI) to form insoluble precipitates (Amonette et al 1994;Fredrickson and Gorby 1996;Deng and Stone 1996).…”
Section: Sulfate Reduction Processmentioning
confidence: 99%